2007
DOI: 10.1124/dmd.106.011478
|View full text |Cite
|
Sign up to set email alerts
|

Independent Regulation of Apical and Basolateral Drug Transporter Expression and Function in Placental Trophoblasts by Cytokines, Steroids, and Growth Factors

Abstract: ABSTRACT:Placental ATP binding cassette (ABC) transporters protect placental and fetal tissues by effluxing xenobiotics and endogenous metabolites. We have investigated the effects of cytokines and survival/growth factors, implicated in various placental pathologies, on ABC transporter expression and function in primary placental trophoblast cells. Treatment of primary term trophoblasts in vitro with tumor necrosis factor-␣ (TNF-␣) or interleukin (IL)-1␤ decreased mRNA and protein expression of apical transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
146
4
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 42 publications
8
146
4
1
Order By: Relevance
“…Interestingly, a down-regulation in Bcrp expression was detected in both the placental trophoblast cells and fetal capillary endothelium of endotoxin-treated animals. A decrease in the in vitro expression of Bcrp in primary term trophoblasts was recently reported after exposure to TNF-␣ or IL-1␤ (Evseenko et al, 2007). Consistent with these in vitro findings, our results demonstrate a significant induction of TNF-␣ and IL-6 in the maternal plasma of endotoxin-treated rats.…”
Section: Effect Of Endotoxin On Placental Drug Transporterssupporting
confidence: 81%
“…Interestingly, a down-regulation in Bcrp expression was detected in both the placental trophoblast cells and fetal capillary endothelium of endotoxin-treated animals. A decrease in the in vitro expression of Bcrp in primary term trophoblasts was recently reported after exposure to TNF-␣ or IL-1␤ (Evseenko et al, 2007). Consistent with these in vitro findings, our results demonstrate a significant induction of TNF-␣ and IL-6 in the maternal plasma of endotoxin-treated rats.…”
Section: Effect Of Endotoxin On Placental Drug Transporterssupporting
confidence: 81%
“…Our findings differ from prior literature reports noting transporter down-regulation during inflammation caused by inflammatory cytokines such as TNF-␣, IL-6, and endotoxin (i.e., LPS) in rats (Sukhai et al, 2001;Chen et al, 2005;Wang et al, 2005) and human primary placental cells (Evseenko et al, 2007). We offer several possible explanations for these differences: the impact of LPS-induced inflammation on drug transporters has yet to be evaluated at different gestational stages, and previous reports have indicated that preterm placentas respond differently to LPS than those at term, specifically in their patterns of cytokine release (Holcberg et al, 2007).…”
Section: Mason Et Alcontrasting
confidence: 56%
“…Cells were collected as mononuclear CTB at 2 h and grown for a further 72 h in M199 media supplemented with 10% FCS, 100 U/ml penicillin and 100 mg/ml streptomycin in 5% CO 2 humidified atmosphere at 37 8C. CTB purity was confirmed by the proportion of CK7-positive trophoblast cells in the culture, which was 95G 3.14% (nZ3) (Evseenko et al 2007a).…”
Section: Third-trimester Placental Ctbsmentioning
confidence: 99%
“…Placentae (nZ10) were obtained with informed consent from women after delivery by Caesarean section at term, and CTBs were isolated using trypsin digestion as described previously (Evseenko et al 2007a). Briefly, villous tissue from term placentae were subjected to eight consecutive digestions in 0.25% trypsin and cells were isolated by centrifugation at 300 g for 7 min.…”
Section: Third-trimester Placental Ctbsmentioning
confidence: 99%